Kontribusi Kecepatan Dan Keseimbangan Tubuh Terhadap Kemampuan Tendangan Depan Atlet Perguruan Kungfu Naga Merah siauw Lim Sie Indonesia Sasana Polres Nias - Ricky Kristian Hulu; Nuridin Widya Pranoto; Septri; Sonya Nelson (Jurnal IKEOR, 2024)
The problem in this study began with the lack of front kick ability of the athletes of the Red Dragon Kungfu School of Siauw Lim Sie Indonesia, Sasana Polres Nias. The purpose of this study was to determine the contribution of speed and body balance to the front kick ability of the athletes of the Red Dragon Kungfu School of Siauw Lim Sie Indonesia, Sasana Polres Nias. This type of research is a correlational method. The sample in this study consisted of 15 athletes of the Red Dragon Kungfu School of Siauw Lim Sie Indonesia, Sasana Polres Nias. The instrument used in measuring speed used a 30-meter sprint test, body balance data used stork stand test data and front kick ability data used a 10-second front kick test. Based on the results of the data analysis, it shows that there is a significant contribution of speed and body balance to the front kick ability of athletes of the Red Dragon Kungfu School of Siauw Lim Sie Indonesia, Sasana Polres Nias by 41.81%. Keywords: Speed, Balance, Front Kick